(untitled) (Progress Annals: Journal of Progressive Research, 2025)
Abu Hafs Nasafi in his work “Kitab al-qand”, cites numerous hadiths reflecting the national and religious values of the peoples of the Central Asian region, which were relevant in the 8th-12th centuries. An analysis of these hadiths reveals that the hadiths transmitted during the initial period of Islam’s introduction to the region were related to issues of theology, Sufism, jurisprudence, and national and religious values.